Metaphysics as Therapy List-Making and Renunciation in Gnostic Yogas - Bouthillette, Karl-Stéphan (Springer Nature Singapore, 2025)
List Making: From Universal to Spiritual Exercise -- Gnostic Yoga as Philosophical Practice -- Case Studies in South Asian Gnostic Spiritual Exercises -- Conclusion.
Keywords: Metaphysics.; Spirituality.